2020
DOI: 10.3390/v12080824
|View full text |Cite
|
Sign up to set email alerts
|

Persistent BK Polyomavirus Viruria Is Associated with Accumulation of VP1 Mutations and Neutralization Escape

Abstract: To investigate the relationship between neutralization escape and persistent high-level BK polyomavirus replication after kidney transplant (KTx), VP1 sequences were determined by Sanger and next-generation sequencing in longitudinal samples from KTx recipients with persistent high-level viruria (non-controllers) compared to patients who suppressed viruria (controllers). The infectivity and neutralization resistance of representative VP1 mutants were investigated using pseudotype viruses. In all patients, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 50 publications
3
38
0
Order By: Relevance
“…The role of Asp69 is not known, but it lies adjacent Neu5Ac binding site, that, as described above, represents a major cell surface interaction compound for MCPyV VP1 [41]. Mutation of D60N (that corresponds with D69 in MCPyV VP1) in combination with K69N, A72V and E82Q in BKPyV VP1 reduced BKPyV infectivity in HEK293TT cells 5-fold compared to BKPyV with wild-type VP1 [45]. The D60N mutation in BKPyV VP1 disrupts the epitope bound by the neutralizing monoclonal 41F17, but the effect of the single D60N mutation on BKPyV infectivity was not tested [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Asp69 is not known, but it lies adjacent Neu5Ac binding site, that, as described above, represents a major cell surface interaction compound for MCPyV VP1 [41]. Mutation of D60N (that corresponds with D69 in MCPyV VP1) in combination with K69N, A72V and E82Q in BKPyV VP1 reduced BKPyV infectivity in HEK293TT cells 5-fold compared to BKPyV with wild-type VP1 [45]. The D60N mutation in BKPyV VP1 disrupts the epitope bound by the neutralizing monoclonal 41F17, but the effect of the single D60N mutation on BKPyV infectivity was not tested [46].…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies showed that persistent high-level BKPyV viruria in renal transplant recipients is associated with accumulation of mutations in VP1 [45,52], longitudinal studies to investigate whether mutations accrue in MCPyV VP1 in individuals with persistent or intermittent shedding of MCPyV should be performed. Moreover, in this study, PCR was used to amplify MCPyV VP1 sequences in the biological samples.…”
Section: Discussionmentioning
confidence: 99%
“…These estimates of repertoire diversity are based on two patients who controlled BKPyV replication, and may not be representative of patients with prolonged PyVAN, in whom virus neutralization escape occurs. As shown in Supplementary Figure 2, patients 3.3 and 3.4 displayed persistent high level BKPyV replication, and we have previously documented neutralization escape in these two patients (McIlroy et al, 2020; Peretti et al, 2018). Unfortunately, the low number of BKPyV-specific antibody sequences obtained from these two patients did not allow us to compare their BCR repertoires with those observed in patients 3.1 and 3.2, and further work will be required to systematically compare virus-specific BCR repertoires between patients with different virological and clinical outcomes.…”
Section: Discussionmentioning
confidence: 59%
“…The plasmid pEGFP-N1 (Clontech) was used as the reporter gene. Plasmids containing mutated VP1 sequences have been described previously were obtained by site-directed mutagenesis using the NEBase changer kit (New England Biolabs) (McIlroy et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, our results add another layer to interpreting the increased risk of BKPyV-DNAemia and nephropathy in KT patients in donor–recipient pairs having BKPyV-serotype mismatch [ 5 ], which has been solely attributed to lacking the corresponding genotype-specific NAbs [ 18 , 21 ]. Conversely, high NAbs in the recipient against the donor genotype may be a marker for matching genotype-specific T-cells [ 26 ], adding to the partial protection and earlier clearance of plasma BKPyV loads in many [ 22 , 49 , 50 ], but not all cases [ 28 ]. Other observational studies can also be discussed in the new light of our findings, which report significant correlations of decreasing BKPyV-specific T-cells from pre-transplant to post-transplant with increased risk [ 12 ].…”
Section: Discussionmentioning
confidence: 99%